Environmental taxation and structural change in an open economy - Böhringer, Christoph,Welsch, Heinz,Löschel, Andreas (ZEW, 2001)
The economic effects of environmental taxes depend on the market structure. Under imperfect competition with free entry and exit, environmental taxes have an impact on economies of scale by changing the number and size of firms. Whether economies of scale rise or fall in a particular industry depends on induced changes in the price elasticity of demand. Because export demand is more price elastic than domestic demand, the overall price elasticity rises (falls) as the industry gains (loses) in comparative advantage. We use a computable general equilibrium model for Germany to examine the effects of a unilaterally introduced carbon tax under both perfect and imperfect competition. Our key finding is that induced structural change in favor of the less energy intensive, more labor intensive industries is more pronounced under imperfect competition than under perfect competition. At the macroeconomic level, the total costs of environmental regulation under imperfect competition can be higher or lower than those under perfect competition depending on whether aggregate gains or losses in economies of scale across imperfectly competitive sectors prevail.
Literaturverz. S. 15 - 17
Keywords: Arbeitspapier; Graue Literatur; Buch; Online-Publikation; Ökosteuer; Umweltabgabe; Steuerwirkung; Faktorintensität; Strukturwandel; Skalenertrag; Komparativer Vorteil; Allgemeines Gleichgewicht; Unvollkommener Wettbewerb; Offene Volkswirtschaft; Theorie